Towards an Integrative Understanding of Diet–Host–Gut Microbiome Interactions - Read, Mark N.; Holmes, Andrew J. (Frontiers in Immunology, 2017)
Over the last 20 years a sizeable body of research has linked the microbiome and host diet to a remarkable diversity of diseases. Yet unifying principles of microbiome assembly or function, at levels required to rationally manipulate a specific individuals’ microbiome to their benefit, have not emerged. A key driver of both community composition and activity is the host diet, but diet-microbiome interactions cannot be characterised without consideration of host-diet interactions such as appetite and digestion. This becomes even more complex if health outcomes are to be explored, as microbes engage in multiple interactions and feedback pathways with the host. Here we review these interactions and set forth the need to build conceptual models of the diet-microbiome-host axes that draw out the key principles governing this system’s dynamics. We highlight how ‘units of response,’ characterisations of similarly behaving microbes, do not correlate consistently with microbial sequence relatedness, raising a challenge for relating high-throughput data sets to conceptual models. Furthermore, they are question-specific; responses to resource environment may be captured at higher taxonomic levels, but capturing microbial products that depend on networks of different interacting populations, such as SCFA production through anaerobic fermentation, can require consideration of the entire community. We posit that integrative approaches to teasing apart diet-microbe-host interactions will help bridge between experimental data sets and conceptual models, and will be of value in formulating predictive models.